The Influence of Social Support on Career Planning with Self-Efficacy as a Mediation Variable in Students of The Department of Management, Padang State University - Dhani, Ilham; Syahrizal, Syahrizal (Human Resource Management Studies, 2024)
This research analyzes: (1) Does social support influence career planning (2) Does social support influence self-efficacy p (3) Does self-efficacy influence career planning (4) Does self-efficacy mediate the relationship between social support influence career planning This research is causal research. The sample for this research was 200 UNP Padang City students. The sampling technique was carried out using the Slovin Technique. Data collection used a questionnaire with a Likert scale. The analysis technique uses SPSS 23 software. The results of this study show that: 1. Partially the Social Support variable has a significant influence on the Career Planning variable, the Social Support variable has a significant influence on the Self-Efficacy variable, the Self-Efficacy variable has a significant influence on the Career Planning variable , The self-efficacy variable is able to mediate the influence of Social Support on the Career Planning variable. The calculation results obtained show that the value of the indirect influence through Self-Efficacy is greater than the value of the direct influence of Social Support on Career Planning.